2020
DOI: 10.1186/s12859-020-3345-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of tumor location in prostate cancer tissue using a machine learning system on gene expression data

Abstract: Background: Finding the tumor location in the prostate is an essential pathological step for prostate cancer diagnosis and treatment. The location of the tumor -the laterality -can be unilateral (the tumor is affecting one side of the prostate), or bilateral on both sides. Nevertheless, the tumor can be overestimated or underestimated by standard screening methods. In this work, a combination of efficient machine learning methods for feature selection and classification are proposed to analyze gene activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…DL has been used for segmentation of the prostate and urethra [ 14 ], for detection of prostate cancer [ 15 ], and for radiation treatment planning for prostate cancer [ 16 ]. However, to our knowledge, there are no reports of the application of DL or artificial intelligence (AI) techniques to improve image quality and evaluate the anatomy and tumors in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DL has been used for segmentation of the prostate and urethra [ 14 ], for detection of prostate cancer [ 15 ], and for radiation treatment planning for prostate cancer [ 16 ]. However, to our knowledge, there are no reports of the application of DL or artificial intelligence (AI) techniques to improve image quality and evaluate the anatomy and tumors in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to promote PC progression and gemcitabine resistance via a HOTTIP-HOXA13 axis route (44). RTN1 (reticulon 1) belongs to the reticulonencoding gene family and is considered as a specific marker and potential therapeutic target for non-small-cell lung cancers, colorectal cancer, and prostate cancer (45)(46)(47)(48). CHRAC1 (Chromatin Accessibility Complex Subunit 1) is a histone-fold protein-encoding gene, functioning in DNA transcription, replication, and packaging as a sequencespecific DNA binding component, and associated with survival progression among breast cancer patients (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 74 ] identified 12 CpG (cytosine and guanine on a genome) site markers and 13 promoter markers, using a deep neural network model, from an initial pool of 139,422 CpG sites, and the promoter methylation data contained 15,316 promoters and applied three machine learning strategies (moderated t-statistics, LASSO, and random-forest).This might further be used for liquid biopsy of cancers. Lately, Hamzeh et al [ 75 ] used a combination of efficient machine learning methods (Support Vector Machine (SVM)-Radial basis function kernel (SVM-RBF), Naive Bayes, Random Forest) to analyze gene activity and to identify the genes for the presence of PCa (on one side or both sides). The highest accuracy and precision for the different classifiers came from the SVM-RBF classifier, which was able to separate the different locations by an accuracy of 99% and found genes (HLA-DMB and EIF4G2) that are correlated with PCa progression.…”
Section: Ai In Prostate Cancer Genomicsmentioning
confidence: 99%